First-line treatment of hepatocellular carcinoma: a propensity-matched analysis of tyrosine kinase inhibitors combined with TACE, with or without PD-1 inhibitors - Shen, Yanjun; Xu, Yawen; Teng, Ying; Ding, Xiaoyan; Chen, Jinglong (Frontiers in Pharmacology, 2025)
ObjectiveThis study attempted to comprehensively assess the clinical outcomes of cases with progressive HCC (pHCC) undergoing treatment with TKI and ICI in conjunction with TACE, as compared to the combination of TKI with TACE alone.MethodsFrom March 2019 to January 2022, this cohort comprised 82 cases who received TACE in conjunction with TKI and 52 cases who were treated with TACE plus TKI alone. The propensity scores was used to mitigate selection bias.ResultsThe multivariate analysis further reinforced that liver cirrhosis (HR = 1.233, 95% CI: 1.024–1.484, P = 0.027), tumor diameter (HR = 1.283, 95% CI: 1.086–1.515, P = 0.003), and the treatment strategy (HR = 0.495, 95% CI: 0.264–0.793, P = 0.000) were independently linked to OS, underscoring their prognostic relevance.ConclusionIncorporating TACE, TKI, and ICI remarkably enhanced both PFS and OS relative to TACE with TKI alone, positioning it as a more efficacious first-line therapeutic strategy for unresectable HCC, while maintaining an acceptable safety profile in clinical settings.